2013
DOI: 10.1007/s11661-013-1928-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Surface Coatings on Preventing Interfacial Reaction During Ultrasonic Welding of Aluminum to Magnesium

Abstract: High power ultrasonic spot welding (USW) is a solid-state joining process that is advantageous for welding difficult dissimilar material couples, like magnesium to aluminum. USW is also a useful technique for testing methods of controlling interfacial reaction in welding as the interface is not greatly displaced by the process. However, the high strain rate deformation in USW has been found to accelerate intermetallic compound (IMC) formation and a thick Al12Mg17 and Al3Mg2 reaction layer forms after relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…For example, previous research that employed a manganese barrier layer produced by physical vapor deposition (PVD) found that thin brittle coatings tended to break up during friction welding, compromising their effectiveness. [15] In this investigation, a potential solution has been examined that combines both the above approaches for controlling the interfacial reaction normally seen in Al to Mg dissimilar welding. Based on thermodynamic considerations (e.g., Reference 20), a ductile Al-Si coating material has been selected to (i) function as a partial diffusion barrier layer, and (ii) preferentially form a new IMC phase that can suppress the formation of the highly brittle Al-Mg intermetallic compounds normally seen at the joint interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous research that employed a manganese barrier layer produced by physical vapor deposition (PVD) found that thin brittle coatings tended to break up during friction welding, compromising their effectiveness. [15] In this investigation, a potential solution has been examined that combines both the above approaches for controlling the interfacial reaction normally seen in Al to Mg dissimilar welding. Based on thermodynamic considerations (e.g., Reference 20), a ductile Al-Si coating material has been selected to (i) function as a partial diffusion barrier layer, and (ii) preferentially form a new IMC phase that can suppress the formation of the highly brittle Al-Mg intermetallic compounds normally seen at the joint interface.…”
Section: Introductionmentioning
confidence: 99%
“…To produce a bond with good mechanical properties, it is usually essential to maintain the IMC layer thickness below a critical value, since IMC phases are typically brittle and can lead to a marked loss in joint toughness if allowed to become too thick. [5][6][7][8] Therefore, many researchers have studied reactive diffusion in a large number of binary alloy diffusion couples and there have also been several attempts to model the evolution of the IMC layer. [1][2][3][4][5] It is widely accepted that reactive diffusion is mainly governed by volume diffusion, [1][2][3]9,10] and the thickness of an IMC phase generally follows a parabolic relationship with annealing time.…”
Section: Introductionmentioning
confidence: 99%
“…The function of ultrasonic assistance used in the process of welding was preliminarily exploded. The first set results, displayed as figure 5, give the fact that ultrasonic assistance indeed have positive effects on joint welding [7,8]. The size of ultrasonic assistance joint reliable area is obviously larger than before with non-ultrasonic assistance in the same parameter 5s, 1.0kA, 0.1Mpa.…”
Section: Resultsmentioning
confidence: 93%